2000
DOI: 10.1095/biolreprod62.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets Containing Gossypol on Reproductive Capacity of Rainbow Trout (Oncorhynchus mykiss)1

Abstract: We evaluated five practical diets in which 0%, 25%, 50%, 75%, and 100% (dietary treatments 1-5) of fish meal protein was replaced by solvent-extracted cottonseed meal protein. Adult rainbow trout (initial average weight 247 +/- 8 g) were fed the diets over a period of 131 days during which a general 2-fold body weight increase occurred. The total diet gossypol concentration (free and protein-bound) showed a gradual increase with increased cottonseed meal substitution. Blood samples were collected on Days 0, 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
7
27
0
Order By: Relevance
“…CO. Similarly, Dabrowski et al (2000) and Lee et al (2002Lee et al ( , 2006 have reported lower hematocrit levels in rainbow trout fed diets containing a high level of oilseed meal (cottonseed meal). The reason for the observed lower hematocrit level could be the cumulative effect of gossypol and/or decreased availability of iron in canola meal leading to lower erythrocyte levels or increased fragility (Colin-Negrete et al 1996).…”
Section: Discussionmentioning
confidence: 91%
“…CO. Similarly, Dabrowski et al (2000) and Lee et al (2002Lee et al ( , 2006 have reported lower hematocrit levels in rainbow trout fed diets containing a high level of oilseed meal (cottonseed meal). The reason for the observed lower hematocrit level could be the cumulative effect of gossypol and/or decreased availability of iron in canola meal leading to lower erythrocyte levels or increased fragility (Colin-Negrete et al 1996).…”
Section: Discussionmentioning
confidence: 91%
“…The same growth performance and feed utilization were observed under these conditions as fi sh fed a complete FM diet during outdoor culture. Large rainbow trout (1.5 year old adults and broodstock) fed CM-containing feed for more than 9 months do not show depressed growth (Dabrowski et al, 2000;Blom et al, 2001;Rinchard et al, 2003;Lee et al, 2006). In contrast, lower growth was observed in both sexes of mature tilapia ( Oreochromis sp.)…”
Section: Discussionmentioning
confidence: 95%
“…Gossypol, a yellow pigment found in the gland of cottonseed, has been demonstrated to be toxic for many fish species 23,27,47,50 . The toxicity of gossypol depends on several factors including the form of gossypol (free or bound form), the amount of consumption and varieties of the cottonseed.…”
Section: Discussionmentioning
confidence: 99%